2022
DOI: 10.3390/educsci12040274
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Modular Robot for Educational Robotics Developed Using Action Research Evaluated on Technology Acceptance Model

Abstract: This research evaluates a novel, modular, open-source, and low-cost educational robotic platform in Educational Robotics and STEM Education. It is the sequel of an action research cycle on which the development of this robot is based. The impetus for the need to develop this came from the evaluation of qualitative and quantitative research data collected during an educational robotics event with significant participation of students in Athens, which showed an intense interest in students in participating in ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…The results of the validity test by employing two expert validators showed that the test was valid based on those domains. Furthermore, the reliability of the test was measured, this refers to the consistency of the measurement [38]. The reliability of the test is calculated according to the percentage of agreement equation of each validator [39], and the result showed the test was reliable.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the validity test by employing two expert validators showed that the test was valid based on those domains. Furthermore, the reliability of the test was measured, this refers to the consistency of the measurement [38]. The reliability of the test is calculated according to the percentage of agreement equation of each validator [39], and the result showed the test was reliable.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Technology Acceptance Model (TAM) proposes that the key factors of system technology acceptance consist of external variables, PEOU, PU, attitudes toward use, and behavioral intentions that together assess the technology acceptance of users in a system ( Davis, 1989 ; Chatzopoulos et al, 2022 ). According to the TAM model theory, people’s technology acceptance can be understood from external variables to internal variables, with PU being how much individuals value the technology they use, and PEOU being how easy individuals perceive the technology to be to operate ( Davis, 1989 ).…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
“…The ESP32 has a low power consumption and low cost intended for internet of things (IoT) and embedded applications and is the successor to the ESP8266.furthermore, ESP32 board can interface with other systems to provide Wi-Fi and Bluetooth functionality through its SPI/SDIO or I2C/UART interfaces. In addition, it is often programmed by an Arduino IDE which allows loading of a program whose language is a set of C/C++ functions into the board by USB cable [21], [22]. In our work we used ESP32 DEVKIT V1-DOIT version with 30 GPIOS.…”
Section: Esp32 Boardmentioning
confidence: 99%